2004
DOI: 10.1177/003804070407700101
|View full text |Cite
|
Sign up to set email alerts
|

Social-Class Differences in Summer Learning Between Kindergarten and First Grade: Model Specification and Estimation

Abstract: Sociologists suggest that children from socially advantaged families continue to learn during the summer, whereas children from disadvantaged families learn either little or lose ground.This disparity in summer learning is hypothesized to result from differential participation in educationally beneficial summer activities. In this article, we test this theory with current and nationally representative data, the Early Childhood Longitudinal Study-Kindergarten Cohort.We examine how children's socioeconomic statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
199
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(219 citation statements)
references
References 23 publications
8
199
2
2
Order By: Relevance
“…Bradley et al (2001) found that nonpoor mothers were more likely than poor mothers to read to their children three or more times per week, with this difference being most pronounced in early childhood. Burkam et al (2004) found that, compared to the middle-SES groups, low-SES parents were significantly less likely to read a book to their child in the summer between kindergarten and first grade, while high-SES parents were more likely to read a book to their child. A similar pattern was evident for taking the child to a library or bookstore.…”
Section: Why Do Low-ses Children Make Less Progress In Reading In Thementioning
confidence: 86%
See 2 more Smart Citations
“…Bradley et al (2001) found that nonpoor mothers were more likely than poor mothers to read to their children three or more times per week, with this difference being most pronounced in early childhood. Burkam et al (2004) found that, compared to the middle-SES groups, low-SES parents were significantly less likely to read a book to their child in the summer between kindergarten and first grade, while high-SES parents were more likely to read a book to their child. A similar pattern was evident for taking the child to a library or bookstore.…”
Section: Why Do Low-ses Children Make Less Progress In Reading In Thementioning
confidence: 86%
“…This subsample of about 4,000 children has allowed at least six sets of investigators to examine learning rates in the summer following kindergarten (Benson & Borman, 2007;Burkam, Ready, Lee, & LoGerfo, 2004;Cheadle, 2008;Downey, von Hippel, & Broh, 2004;LoGerfo et al, 2006;McCoach, O'Connell, Reis, & Levitt, 2006). These studies found no summer gains in reading for all children and significant differences by SES group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, promising evidence suggests that summer programs may be one way to support children's learning and development (Kim and Quinn, 2013;Terzian, Moore, and Hamilton, 2009). Some children, particularly those from low-income households, learn very little or lose ground over the summer (Alexander, Entwisle, and Olson, 2001;Burkam et al, 2004). Enriching summer programs may help keep children on an upward learning trajectory in the summer months (Terzian, Moore, and Hamilton, 2009).…”
Section: Motivating Research Literaturementioning
confidence: 99%
“…Some studies have estimated that this loss is large: "the summer loss equaled about one month on a gradelevel equivalent scale, or one tenth of a standard deviation relative to spring test scores" (Cooper et al 1996). Several studies document declines in student test scores over the summer that are larger for disadvantaged and minority students (O'Brien, 1999;Burkam et al, 2003;Downey, Hippel, & Broh, 2004;Alexander, Entwisle, & Olson, 2007).…”
Section: Introductionmentioning
confidence: 99%